EROSION HAZARD ANALYSIS USING SPATIAL MODELING: A CASE STUDY OF THE TEMBESI WATERSHED, SAROLANGUN REGENCY, JAMBI PROVINCE - Fadhila Afnan; Dasrizal Dasrizal; Erna Juita (Geographica: Science and Education Journal, 2022)
The formulation of the problem in this study is the characteristics of erosion, the level of erosion hazard, and the spatial model of erosion hazard in the Tembesi watershed, Sarolangun Regency, Jambi Province. Then the main purpose of this study is to determine the level of erosion hazard at the research location points, which will then be spatialized using ArcGIS 10.4. In this study, the research method used is the descriptive qualitative method. Because seeing the information and description of the level of erosion hazard in the Tembesi watershed, Sarolangun Regency, Jambi Province. The data of this study include primary data, namely direct measurements and observations in the field and secondary data, namely data obtained through the relevant agencies. The results obtained in this study are: First, the erosion characteristics at the research location points have two dimensions, namely V and U-shaped dimensions with a depth of 30 cm and some 30cm. Second, the erosion hazard level was calculated using the USLE method, with the results at the research site points 2.00 tons/ha/year. Third, the spatial model used in this research is Arc GIS 10.4. With each level of erosion, hazards are 5.87 (very mild), 29.36 (mild), 2.94 (very light), 2.94 (very mild), 5.87 (very mild), 29, 36 (light), and 205.52 (heavy).